Homologation Decision Against Creditors Who Did Participate in The Peace Agreement (Case Study: Decision Number 993 K/Pdt.Sus Bankruptcy/2019) - Andi Deswanta; Agung Iriantoro; Watcharee Ariyamang (Journal Evidence Of Law, 2025)
Homologation decisions in the Debt Payment Obligation Postponement (PKPU) system have universal binding force which creates legal complexity, especially regarding the protection of creditors who do not participate in the peace agreement. This research analyzes the legal force of homologation decisions and protection mechanisms for non-participating creditors based on the Indonesian bankruptcy system through a case study of Supreme Court Decision Number 993 K/Pdt.Sus-Bankruptcy/2019. The research method used is normative legal research with statutory and conceptual approaches. The results showed that the homologation decision has a fundamental position as an instrument of judicial ratification that transforms the peace agreement into a court decision with an executorial title and universal binding force. Its legal legitimacy is obtained through the fulfillment of quorum and majority requirements in Article 281 of the PKPU Law which applies a dual majority requirement system. However, legal protection for non-participating creditors faces significant limitations as the principle of universal binding force creates complex legal implications, ranging from loss of contractual autonomy to changes in the legal status of receivables. Although there is a cassation remedy mechanism available, in judicial practice such protection is limited to procedural aspects with a high threshold for success, so that the Indonesian PKPU system prioritizes the efficiency of collective settlements over the substantive protection of minority creditors